The Successor Training as a Success Factor in the Management and Continuity of the Family Business - Luz del Carmen García Arroyo; Montserrat Gómez- Márquez; Martha Patrícia Quintero- Fuentes; Manuel González- Pérez (European Scientific Journal, ESJ, 2020)
The formation of the successor is a process that begins at home from an early age, and its main objective is to preserve the family legacy and keep the company's administration in the hands of the family. The family business's continuity depends mainly on the training received by their predecessors' successors to replace them in business management when retirement them. A descriptive and cross-sectional study was carried out that identified the influence of the successors' formation to achieve success in business management and the family business's continuity. This study collected data from 15 family businesses located in southeastern Mexico. The data collection instrument used was a closed-order questionnaire that was validated using Pearson's correlation. The chi-square test of statistical independence generates the calculation of the dependency between the variables studied. The theoretical chi-square graph is the pair of variables that make up the hypothesis and its theoretical inverse function: p-value = 0.05 vs. chi-square of 1 degree of freedom to observe the intersection. In conclusion, the statistical tests yielded six variables more dependent on each other. Items three and four, four and one, and two and seven associated with 95% reliability in theoretical or critical chi and 100% reliability in observed or experimental chi. Therefore, these results found are statistically significant. It observed that the training of successors influences business management's success and the family business's continuity. This hypothesis verified an observed or experimental chi value of 5.2387 and a theoretical or critical chi of 3.8415.